2022
DOI: 10.36987/jes.v9i1.2588
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Reading Comprehension Achievement at Second Semester Students of Bhinneka Pgri University in the Academic Year 2020/2021

Abstract: To reading comprehension, especially long texts in foreign languages, some students have problems, such as being lazy and bored. If this problem persists, it will affect student achievement. This study was conducted with the aim of (1) to find how is the students’ reading comprehension achievement at second semester of Bhinneka PGRI University in the academic year 2020/2021. (2) to find what are the factors that affect the students’ reading comprehension achievement at second semester students of Bhinneka PGRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…By reading, humans can comprehend the writing around them. As stated by Rupley et al (Agustin and Huda, 2022) that reading ability gives many advantages. In reading activity, readers can get some knowledge and some important information.…”
Section: Introductionmentioning
confidence: 97%
“…By reading, humans can comprehend the writing around them. As stated by Rupley et al (Agustin and Huda, 2022) that reading ability gives many advantages. In reading activity, readers can get some knowledge and some important information.…”
Section: Introductionmentioning
confidence: 97%
“…Dewi & Rahmawati (2021) reported that students often experienced boredom and lack of motivation while reading, leading to disengagement. Agustin (2022) discovered that students frequently faced challenges in understanding text content, experiencing boredom, fatigue, and difficulties. Silalahi et al (2022) highlighted students' lack of comprehension in reading processes such as decoding, hindering their understanding of specific information and the main ideas of texts, leading to confusion.…”
Section: Introductionmentioning
confidence: 99%